1997
DOI: 10.1051/jp4:1997404
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Arc Cathode Spots

Abstract: Arc cathode spots operating by formation of surface-microplasmas are reviewed for discharges in vacuum and in gases. New experimental studies using advanced optical methods (image converter cameras and laser absorption techniques) reveal that the spot is composed of fragments with a size below 10 pm. In vacuum these are highly mobile, for copper on a rime scale < 50 ns. The motion and the rapid sequences of extinctions and re-ignitions determine the behavior of the whole spot. Cu-spots in vacuum exhibit displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…During the last decade, experimental evidence has been collected confirming the existence of fragments (microspots) in discharges on cold cathodes and, thus, supporting the second point of view insofar as cold cathodes are concerned; see, e.g., [18] and references therein. No unambiguous evidence of such type has been obtained for hot cathodes.…”
Section: Concepts Of Near-cathode Phenomena In Arc Dischargesmentioning
confidence: 81%
See 1 more Smart Citation
“…During the last decade, experimental evidence has been collected confirming the existence of fragments (microspots) in discharges on cold cathodes and, thus, supporting the second point of view insofar as cold cathodes are concerned; see, e.g., [18] and references therein. No unambiguous evidence of such type has been obtained for hot cathodes.…”
Section: Concepts Of Near-cathode Phenomena In Arc Dischargesmentioning
confidence: 81%
“…Reviews of early works in which such an approach was used can be found in [8]- [13]; models specifically designed for cathodes of HID lamps are presented in [14] and [15] (see also [16], in which the model of [14] is reconstructed). Second, there are works in which plasma-cathode interaction is considered as a sequence of individual events (termed by different authors as microexplosions, or microspots, or fragments) occurring on extremely small length and time scales of the orders of micrometers and nanoseconds, respectively; see, e.g., the reviews of [17] and [18]. While models considered in the framework of the first approach are stationary or quasi-stationary, models considered in the framework of the second approach are essentially nonstationary.…”
Section: Concepts Of Near-cathode Phenomena In Arc Dischargesmentioning
confidence: 99%
“…Hence, ̇ ⁄ . We next assume that this mass is expelled by the thruster in the form of doubly-ionized Titanium ions [8]. The corresponding current is thus…”
Section: Ii3 Simulation Inputsmentioning
confidence: 99%
“…В воздухе поверхность электродов покрыта оксидами [15]. В [16] были обнаружены пленки азота толщиной 10 nm при давлении 670 Pa и толщиной два раза большей при давлении 1300 Pa. В [15,17,18] изучали влияние слоев загрязнения на типы пятен и их движение. Было обнаружено, что при увеличении давления газа начинают преобладать пятна первого типа, т. е. поверхностные загрязнения способствуют зажиганию новых КП на больших расстояниях от существующего.…”
Section: Introductionunclassified